"Reason's sympathy" and others' ends in Kant. (1st June 2021) - Vilhauer, Benjamin
Abstract: Kant's notion of (what I will call) rational sympathy solves a problem about how we can voluntarily fulfill our imperfect duty to adopt those ends of others which have value only because they have been set by rational agents, ends which I will refer to as merely permissible ends (MPEs). Others' MPEs are individuated in terms of their own concepts of their MPEs, and we can only adopt their MPEs in terms of their concepts, since to adopt them in terms of different concepts would be to adopt different ends. Others' concepts of their MPEs may contain marks of the first person, and should contain no marks of law apart from permissibility. Rational sympathy allows us to adopt ends individuated in terms of concepts with marks of these kinds because rational sympathy allows us to voluntarily adopt others' first‐person perspectives in imagination, and to voluntarily shape our contingent feelings so that such concepts motivate us despite their underdetermination by law.